PROPERTY VIOLENCE AGAINST WOMEN IN MANAUS, AMAZONAS: ANALYSIS OF PUBLIC PREVENTION AND PROTECTION POLICIES IN THE CONTEXT OF DOMESTIC AND FAMILY VIOLENCE - Campos, Dayla Corrêa; da Silva, Anacarla Cezario; Valente, Charles Ulisses Vieitas; Rodrigues, João Lopes; de Aguiar, João Vitor Gomes; Ricardo, Nicolly Falcão; Fonseca, Sulyvan Micael Barbosa; Duarte, Susamara Silva; Freitas, Tayla Guimarães; de Oliveira, Thaís Bentes; Gonçalves, Dimas Melo (Seven Editora, 2026)
Domestic and family violence against women represents one of the most significant social and legal issues in contemporary society, directly affecting women’s dignity, autonomy, and fundamental rights. Among the different forms of violence established under Brazilian legislation, property violence stands out due to its ability to restrict victims’ economic independence and perpetuate abusive relationships marked by financial control and economic dependence. In this context, the present study aimed to analyze public policies for the prevention and confrontation of domestic and family violence against women, with emphasis on property violence in the city of Manaus, Amazonas. The research is characterized as a literature review, with a qualitative nature and a descriptive and analytical approach, developed through scientific articles, institutional documents, and technical reports published within the last five years. The results revealed that property violence remains socially and institutionally invisible in several contexts, making its identification and confrontation by public agencies more difficult. It was also observed that factors such as social vulnerability, economic dependence, and structural limitations within the protection network contribute to increasing the difficulties faced by women victims of domestic violence in the Amazon region. It is concluded that strengthening preventive public policies, intersectoral state action, and mechanisms aimed at women’s financial autonomy constitutes an essential measure for reducing property violence and ensuring the effective protection of women’s rights.